The use of the gravity model in forecasting the flows of emigrants in EU countries - Iancu, Nicolaie; Badulescu, Alina; Urziceanu, Ramona-Mihaela; Iancu, Elena-Ana; Simut, Ramona (Technological and Economic Development of Economy, 2017)
Migration is a complex phenomenon with economic, social, political, cultural and human implications, and therefore, it is the locus of interest for many researchers from various fields. After 1989, migration in Romania became a social issue due to the large number of migrants searching for labour all around Europe. This paper focuses on investigating and forecasting labour migration from Romania and its geographical orientation. We analysed the gravity model, which simple and accurate, focused on the distance as a determinant of the length of the mobility and, thus, of the host country chosen by the migrant. Based on the proposed macroeconomic model, we discuss results for main destinations countries, i.e. Spain, Italy, Austria, Germany, as well as for EU as a whole.